2006
DOI: 10.1080/08958370500282928
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Damage Secondary to Occupational Exposure to Tin Vapor

Abstract: Tin is commonly used as a coating on copper kitchen appliances, and "tinsmithing" as a trade is common in many non-Western countries, where cooking utensils are re-tinned when the cooking surface wears thin. Tinsmiths, or "tinkers," are commonly exposed to the following fumes during their work: stannic [tin(IV)] oxide, ammonium chloride, and hydrochloric acid. In this study we assessed workers from tinsmith workshops of our province for signs, symptoms, and laboratory evidence of cardiac end-organ damage. Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We found that exposure to tin in PM 2.5 was negatively associated with HDL-C levels. As far as we know, only one previous study conducted in Turkey estimated lipid effects of tin exposure, 57 but no significant difference was detected between the workers exposed to tin vapor and the control group. We found a positive association between nickel in PM 2.5 and HDL-C. No previous human study explored this topic and thus it is hard for us to compare our findings with others.…”
Section: ■ Discussionmentioning
confidence: 86%
“…We found that exposure to tin in PM 2.5 was negatively associated with HDL-C levels. As far as we know, only one previous study conducted in Turkey estimated lipid effects of tin exposure, 57 but no significant difference was detected between the workers exposed to tin vapor and the control group. We found a positive association between nickel in PM 2.5 and HDL-C. No previous human study explored this topic and thus it is hard for us to compare our findings with others.…”
Section: ■ Discussionmentioning
confidence: 86%